Assessment Relationship Between Components of the World's Leading Stock Indices in Reflection on the World Financial Market Dynamics - Lyashenko, Vyacheslav; Sergienko, Olena; Bilotserkivskyi, Oleksandr (My University, 2021)
The development of the global economy presupposes the stable functioning of all its constituent parts, institutions, and markets. Among such markets of the global economy, a special place is occupied by the financial market, which is able to redistribute financial resources. However, such redistribution must be protected from various risks, unfavorable development of negative situations. To solve such problems, the concept of stock indices is used, which reflects the dynamics of price changes for different groups of securities. Knowing the dynamics of the values of stock indices, one can analyze and predict the development of the financial market as a whole. It is also necessary to take into account the relationship of stock indices and the relationship between the components of various stock indices. Based on this, the paper examines a qualitative assessment of the relationship between the components of the world's leading stock indices in reflecting the dynamics of the world financial market. It is proposed to consider such a qualitative estimate taking into account the wavelet coherence. To this end, the paper proposes a general approach to considering a qualitative assessment of the relationship between the components of the world's leading stock indices. The paper considers real data in the context of various world stock indices, presents research results, and draws general conclusions.
Keywords: valuation; risk; stock index; financial market; securities; wavelet analysis